HUBUNGAN PENERAPAN SEKOLAH LAPANG â€œSRI-ORGANIKâ€ UNTUK KEMANDIRIAN PETANI BERWAWASAN AGRIBISNIS - SUSWADI SUSWADI; MAHANANTO MAHANANTO (Fakultas Pertanian, Universitas Tunas Pembangunan Surakarta, 2014)
Boyolali is one of the Rice Granary and the National Central Java, because its results could be sufficient paddy rice for the Boyolali and there is a surplus of more than 64,000 tons of paddy / her year, but with climate change makes the rainy and dry seasons are not clearly came from. This resulted in a decrease in rice production up to 10-20% so that endanger regional and national food security. Farmers have only depend on the government for assistance and solutions in solving the problem. While the government can address the lack of fast, could not give a good solution to the farmers. This can happen because the extension method that has been done only for the transfer of technology for solving problems that only a moment, and if there is a new problem, farmers can not do anything about it. Field School